2020
DOI: 10.1002/job.2446
|View full text |Cite
|
Sign up to set email alerts
|

Human capital resource emergence and leadership

Abstract: Summary Drawing on multilevel theory of human capital resource emergence (HCRE), this paper reviews existing empirical research to better understand the effect of leadership on this emergence process. Specifically, we summarize the current literature pertaining to how leaders may impact the process through which individual‐level human capital—the knowledge, skills, and abilities of individuals—emerges into a valuable unit‐level human capital resource. We review 132 empirical articles and examine how leadership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 167 publications
(242 reference statements)
0
6
0
Order By: Relevance
“…Last, an emphasis on simple rules in theory may aide in uncovering potential universal factors associated with many emergent phenomena in organizations. It is increasingly acknowledged that several unit-level emergent states have interconnected elements (Eckardt et al, in press; Eckardt & Jiang, 2019; Kozlowski, 2019), and this may mean there is overlap in the underlying simple rules guiding behavior. Wolfram (2002) is also explicit about this potential benefit:The simpler a structure is, the more likely it is that it will show up in a wide diversity of different places.…”
Section: The Futurementioning
confidence: 99%
“…Last, an emphasis on simple rules in theory may aide in uncovering potential universal factors associated with many emergent phenomena in organizations. It is increasingly acknowledged that several unit-level emergent states have interconnected elements (Eckardt et al, in press; Eckardt & Jiang, 2019; Kozlowski, 2019), and this may mean there is overlap in the underlying simple rules guiding behavior. Wolfram (2002) is also explicit about this potential benefit:The simpler a structure is, the more likely it is that it will show up in a wide diversity of different places.…”
Section: The Futurementioning
confidence: 99%
“…For example, a summary of the experience from the American Human Resource Management Program noted that positive leadership helped leaders to coordinate various departments and optimize their functions to solve human resource crises in healthcare ( Sherk et al, 2009 ). A literature review of human capital resources suggested that managers with positive leadership were able to coordinate the organizational human resource management process and strengthen the performance assessment system related to financial distribution ( Eckardt et al, 2020 ). Research on emergency management in elderly healthcare from America confirmed that rapid coordination of intensive care beds and reasonable allocation of ventilator use during the epidemic relied on physicians’ emergency response capacity of positive leadership ( Aitken and Ibrahim, 2021 ).…”
Section: Theoretical Basismentioning
confidence: 99%
“…Second, we complement this approach by leveraging recent reviews of HCR (Ray, Essman, et al, 2023;L. Zhang et al, 2023), HRM (Boon et al, 2018(Boon et al, , 2019, and leadership (Eckardt et al, 2021) to identify theoretical developments and empirical primary studies at the intersection of HRM and leadership to evaluate potential relationships with unit HCR elements. It is important to note that while many studies do not adopt HCR terminology, they are nonetheless relevant to affecting unit HCR elements.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…HRM practices can support these efforts by providing unit leaders with the tools to enhance unit members’ abilities, motivation, and opportunities (Jiang, Lepak, Hu, & Baer, 2012; Lepak et al, 2006). Unit leader behaviors, beyond HRM practice delivery, play critical roles in developing unit HCR and orchestrating their efforts to realize their potential (Eckardt et al, 2021; Ray, Essman, et al, 2023; Wolfson & Mathieu, 2021). We aim to integrate insights from the unit leadership and HRM literatures to explain how unit leaders can use HRM practices in concert with their leadership behaviors to create and capitalize on unit HCR.…”
mentioning
confidence: 99%
See 1 more Smart Citation